3D printed hydroxyapatite composite scaffolds with enhanced mechanical properties. Issue 8 (1st June 2019) - Chen, Shangsi; Shi, Yufei; Zhang, Xin; Ma, Jun
Abstract: Highly porous hydroxyapatite composite scaffolds have limited use in the application in bone tissue engineering due to their poor mechanical properties. The present study investigated the fabrication of hydroxyapatite composite scaffolds with macro porosity (∼600 μm) by means of 3D printing techniques. The obtained scaffolds were characterized concerning their morphology, composition and mechanical properties. It was shown that the compressive properties of scaffolds depended on their composition and inter-layer angle. The ultimate compressive strength of composite scaffolds containing 70 wt% hydroxyapatite reached 14.3 MPa after optimization. The 3D printed composite scaffolds resulted in comparable mechanical properties with cancellous bone, which could extend their potential application in bone repair and regeneration.